Effect of Thyroxine Tablets Treatment on the Oxidative Stress in Hypothyroid Women - Al-Shimaysawee Sadeq (Journal of Global Pharma Technology, 2018)
Objective: Although some researches informed increased oxidative stress (OS) in hypothyroidism, the influence of treatment with levothyroxine is did not considered widely. Hence, we directed this article to examine the influence of levothyroxine therapy on oxidative stress in hypothyroid women. Methods: The current study included 42 women hypothyroid patients treated with thyroxine& 25 untreated in addition to 40, age matched healthy females used as a control group. The thyroid function test, serum reduced glutathione (GSH), catalase (CAT) and glutathione-S-transferases (GST) levels were measured. Results: The results showed that serum GSH level revealed significant increases in hypothyroid untreated patients. In contrast, GSH treated level showed nonsignificant increases when compared with those of the control group, but the results of CAT levels failed to indicate significant variation in the two groups while the serum GST level revealed significant decreases in hypothyroid untreated patients in contrast, GST treated level showed nonsignificant increases when compared with those of the control group. Highly significant (p<0.01) positive correlation was obtained for GSH levels with thyroxine in treated hypothyroid women whereas CAT levels failed to exhibit significant correlation with throxine tablets treatment also Significant (p<0.05) positive correlation was obtained for GST levels with thyroxine in treated hypothyroid women. Conclusions: Hypothyroidism is associated with elevated oxidative stress and thyroxine tablets are modulate the oxidative stress in treated hypothyroid women patients. Keywords: Thyroxine Tablets, Oxidative Stress, Hypothyroid Women.